Low-temperature formation of the FePt phase in the presence of an intermediate Au layer in Pt /Au /Fe thin films. (9th December 2015) - Vladymyrskyi, I A; Gafarov, A E; Burmak, A P; Sidorenko, S I; Katona, G L; Safonova, N Y; Ganss, F; Beddies, G; Albrecht, M; Makogon, Yu N; Beke, D L
Abstract: Pt /Fe and Pt /Au /Fe layered films were deposited at room temperature by dc magnetron sputtering on Al2 O3 (0 0 0 1) single crystalline substrates and heat treated in vacuum at 330 °C with different durations (up to 62 h). It is shown by secondary neutral mass spectrometry depth profiling and x-ray diffraction that the introduction of an additional Au layer between Pt /Fe layers leads to enhanced intermixing and formation of the partially chemically ordered L 10 FePt phase. The underlying diffusion processes can be explained by the grain boundary diffusion induced reaction layer formation mechanism. During the solid state reaction between Pt and Fe, the Au layer moves towards the substrate interface replacing the Fe layer. This was explained by the much faster diffusion of Fe, as compared to Pt, along the grain boundaries in Au. Enhancement of the process and formation of the ordered FePt phase in the presence of the Au intermediate layer were interpreted by the effect of stress accumulation during the grain boundary reactions: the disordered FePt phase formed initially at different Au and Pt grain boundaries can experience appropriate compressive stress along the 1 0 0 directions, which can initiate the formation of the chemically ordered L 10 FePt phase.